ChemInform Abstract: Design, Synthesis and Structure—Activity Relationships of 3, 5‐Diaryl‐1H‐pyrazoles as Inhibitors of Arylamine N‐Acetyltransferase. Issue 36 (15th August 2013) - Fullam, Elizabeth; Talbot, James; Abuhammed, Areej; Westwood, Isaac; Davies, Stephen G.; Russell, Angela J.; Sim, Edith
Abstract A series of pyrazole compounds (III) is synthesized.